2014
DOI: 10.1139/cjpp-2013-0446
|View full text |Cite
|
Sign up to set email alerts
|

Behavioural, metabolic, and endothelial effects of the TNF-α suppressor thalidomide on rats subjected to chronic mild stress and fed an atherogenic diet

Abstract: There is accumulating evidence suggesting that depression is a risk factor for cardiovascular diseases. This study aimed to examine the hypothesis that the proinflammatory cytokine TNF-α would partially explain the link between depression and atherosclerotic endothelial changes. Rats were distributed among 6 groups: (i) control group; (ii) group subjected to chronic mild stress (CMS); (iii) group fed a cholesterol-cholic acid-thiouracil (CCT diet); and (iv) CMS group fed the CCT diet and treated with the vehic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…Ananloo et al [ 42 ] reported increased serum total cholesterol, triglyceride and body weight in depressive patients treated with imipramine. Indeed, previous reports revealed imipramine-induced dyslipidemia, insulin resistance and endothelial dysfunction in CMS model [ 53 ], but this is the first study showing this observation in CRS paradigm.…”
Section: Discussionmentioning
confidence: 68%
“…Ananloo et al [ 42 ] reported increased serum total cholesterol, triglyceride and body weight in depressive patients treated with imipramine. Indeed, previous reports revealed imipramine-induced dyslipidemia, insulin resistance and endothelial dysfunction in CMS model [ 53 ], but this is the first study showing this observation in CRS paradigm.…”
Section: Discussionmentioning
confidence: 68%
“…Literature data show that the chronic IMIP treatment improved chronic stress/ high fat diet-related behavioral changes [31].…”
Section: Discussionmentioning
confidence: 99%
“…In another study, imipramine did not reduce the expression of the chemokine IP-10 and of three mitogen-activated protein kinase (MAPK) pathways, in Th1 LPS-stimulated human monocytes [ 43 ]. Importantly, imipramine impaired acetylcholine-mediated aortic relaxation despite decreasing TNF-α mRNA levels in the aorta of male Wistar rats on a high fat diet [ 59 ].…”
Section: The Effect Of Antidepressant Treatment On Arteriosclerotic Processes: Experimental Datamentioning
confidence: 99%